Analysis of the Implementation of Training on Digital-based Learning Media to Enhance Teachers’ Digital Literacy - Sri Nurhayati; Anggi Fitri; Rudi Amir; Zalisman Zalisman (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aimed to analyze the implementation process, impact of digital-based learning media training on Tahfiz teachers' digital literacy and identified factors influencing the success or limitations of these programs. Utilizing a descriptive method, the study encompassed observations, interviews, and document analysis involving five Tahfiz teachers, a training manager, and a school administrator. The data analysis procedure followed the Miles and Huberman model, comprising three key stages: data reduction, data display, and conclusion drawing, underpinned by triangulation for validity. The findings revealed that the training enhanced teachers' access to digital resources, flexibility in learning, and provided personalized, interactive learning experiences. However, challenges like limited technology access, lack of technical skills, resistance to change, and inadequate resources tailored to Islamic values were notable. The study concludes that comprehensive training in digital literacy is crucial for Tahfiz teachers to effectively integrate technology into their teaching. The study contributes to the discourse on technology integration in religious education, offering insights for policy and practice in Tahfiz education.